Lack of association between human papillomavirus infection and colorectal cancer - Taherian, Hanieh; Tafvizi, Farzaneh; Fard, Zahra Tahmasebi; Abdirad, Afshin (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction : Colorectal cancer is the third leading cause of cancer-related deaths worldwide, with nearly one million new cases identified annually. Different factors might cause colorectal cancer, one of the most prevalent cancers among both men and women. Viral aetiology in cancerous malignancies is a very important issue and so far a number of viral strains have been identified as tumour oncogene viruses. Viral infections, such as human papillomavirus (HPV), have recently been suggested as a risk factor for colorectal cancer. However, the aetiology of the disease is still unknown. Aim : To assessed the association between HPV infection and colorectal cancer. Material and methods : In this study, 50 cancer tissue samples and 50 samples without colon cancer were studied in order to identify HPV through polymerase chain reaction (PCR). Of 42 adenocarcinomas, 10 were well differentiated, 30 moderated differentiated, and 2 were poorly differentiated. DNA extraction was verified by beta globin gene amplification; specific PCR was carried out based on HPV L1 consensus primers MY09/MY11. Results: HPV DNA was not identified in any of the normal, adenocarcinoma, or adenoma samples. Conclusions : In contrast with previous studies, the current research failed to establish a relationship between HPV infection and the incidence of colon cancer. Considering the existing inconsistencies, it is recommended that further studies be conducted with larger sample size.